2020
DOI: 10.3390/ani10040547
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenome Diversity and Maternal Origins of Guangxi Buffalo Breeds

Abstract: Guangxi Province, in the southwest of China, is one of the putative migratory corridors or domestication centers for swamp buffalo. In this study, we investigated the evolutionary status of two Guangxi native buffalo breeds (Fuzhong buffalo, n = 15; Xilin buffalo, n = 25) based on the complete mitogenome sequencing. Our results revealed rich genetic diversity in the two buffalo breeds. We detected five haplogroups (SA1, SA2, SB1, SB2, SB3) in the two Guangxi buffalo breeds, and the haplogroup SB3 in the Fuzhon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Yaks in Qinghai were also close to the wild yak distribution range, suggesting that Qinghai was likely the site of initial yak domestication [ 30 ]. All yaks were divided into three haplogroups; two of these haplogroups (A and B) showed a star-shaped distribution of mitotypes, which was typical of domestic species and consistent with population expansion [ 34 ]. The central mitotypes of A and B were widely distributed and had a high frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Yaks in Qinghai were also close to the wild yak distribution range, suggesting that Qinghai was likely the site of initial yak domestication [ 30 ]. All yaks were divided into three haplogroups; two of these haplogroups (A and B) showed a star-shaped distribution of mitotypes, which was typical of domestic species and consistent with population expansion [ 34 ]. The central mitotypes of A and B were widely distributed and had a high frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The swamp buffalo was most likely domesticated near the border between China and Indochina at ∼3,000-7,000 years BP, spreading across Southeast Asia. Swamp buffaloes have strong phenotypic uniformity, but molecular studies show a higher diversity of maternal and paternal lineages, strong genetic differentiation affected by geography, and a lack of gene flow (27,28). One large study with 46 buffalo populations in seven Asian countries revealed an abundant genetic diversity and clear phylogeographic structure in swamp buffalo populations (29).…”
Section: Water Buffalo Domesticationmentioning
confidence: 99%
“…Other breeds include the Fuzhong and Xilin breeds from Guanxi province, Enshi breed from Hubei, Dongliu breed from Anhui province, and the Shanghai breed. Swamp breeds in China are mainly used for draft purposes as they are very efficient in the marshlands, particularly in rice fields, and have limited milk production capacity (10,28).…”
Section: Water Buffalo Breedsmentioning
confidence: 99%
“…Yaks in Qinghai were also close to the wild yak distribution range, suggesting that Qinghai was likely the site of initial yak domestication [35]. All yaks were divided into six haplotype groups; four of these haplotype groups (A, B, C, and D) showed star-shaped distribution of haplotypes, which was typical of domestic species and consistent with population expansion [39]. The central haplotypes of A, B, C, and D were widely distributed and had a high frequency.…”
Section: Discussionmentioning
confidence: 71%